2012
DOI: 10.1177/0884533612449488
|View full text |Cite
|
Sign up to set email alerts
|

Constipation Is More Frequent Than Diarrhea in Patients Fed Exclusively by Enteral Nutrition

Abstract: Background:Digestive complications in enteral nutrition (EN) can negatively affect the nutrition clinical outcome of hospitalized patients. Diarrhea and constipation are intestinal motility disorders associated with pharmacotherapy, hydration, nutrition status, and age. The aim of this study was to analyze the frequency of these intestinal motility disorders in patients receiving EN and assess risk factors associated with diarrhea and constipation in hospitalized patients receiving exclusive EN therapy in a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Intestinal disorders are one of the most common complications of EN (11), and are reported to affect 30-60% of patients (1,11). Constipation, meanwhile, is very common in patients with reduced mobility (12), and is sometimes even more prevalent than diarrhea in patients receiving enteral feeding alone (13). These complications, aside from the immediate discomfort they cause for patients, can trigger additional problems: adequate nutrition may be limited and electrolyte imbalances may occur, generating additional costs associated with patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal disorders are one of the most common complications of EN (11), and are reported to affect 30-60% of patients (1,11). Constipation, meanwhile, is very common in patients with reduced mobility (12), and is sometimes even more prevalent than diarrhea in patients receiving enteral feeding alone (13). These complications, aside from the immediate discomfort they cause for patients, can trigger additional problems: adequate nutrition may be limited and electrolyte imbalances may occur, generating additional costs associated with patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Many definitions of constipation exist, although most consistently identify infrequent and difficult defecation as defining characteristics 114 . The main causes of constipation among patients receiving EN are medications (benzodiazepines and opioids being the most common), inadequate fluid intake or dehydration, inadequate fiber intake, and lack of physical activity 67 , 73 , 112 . Other causes of constipation include neuromuscular disorders, hypothyroid disorders, GI motility disorders, and history of laxative abuse 112 .…”
Section: Monitoring Troubleshooting and Managing Complicationsmentioning
confidence: 99%
“…Constipation can cause abdominal distension or bloating, vomiting, fecal impaction, and bowel perforation, therefore increasing the need for nursing, medical, and/or pharmaceutical interventions 74 . For these reasons, constipation has been associated not only with feeding intolerance and delays in EN therapy but also with difficulty weaning from mechanical ventilation in critically ill patients, longer length of ICU stay, and decreased quality of life 73 – 75…”
Section: Monitoring Troubleshooting and Managing Complicationsmentioning
confidence: 99%
“…One the other hand, the values in 2010 (10.5%) and 2012 (10.7%) were bordering the target established. Bittencourt et al (41), in an observational study with 110 patients, applied the diarrhea indicator and found a prevalence of 13%, while Martins et al (27) met 8%. In the literature, there are records with higher percentages of episodes of diarrhea, with values ranging from 14% to 41% of the days on ENT (41).…”
Section: Quality Indicators For Enteral and Parenteral Nutrition Thermentioning
confidence: 99%